2013
DOI: 10.1016/j.ijid.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Invasive aspergillosis in patients with hematological malignancies in the Czech and Slovak republics: Fungal InfectioN Database (FIND) analysis, 2005–2009

Abstract: Our retrospective analysis identified key diagnostic and treatment characteristics, and this understanding could improve the management of hematological malignancy patients with IA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…BAL was performed in 69% of the patients with a lower respiratory tract involvement. This rate is high compared to published data and facilitated the identification of pulmonary coinfections in our cohort [24,25]. These data confirm the critical role of BAL in the investigation of pulmonary CT abnormalities in immunocompromised patients; it improved the accurate diagnosis rate of pulmonary IA, with one in five cases diagnosed by BALF analysis only, and identified co-pathogens.…”
Section: Discussionsupporting
confidence: 85%
“…BAL was performed in 69% of the patients with a lower respiratory tract involvement. This rate is high compared to published data and facilitated the identification of pulmonary coinfections in our cohort [24,25]. These data confirm the critical role of BAL in the investigation of pulmonary CT abnormalities in immunocompromised patients; it improved the accurate diagnosis rate of pulmonary IA, with one in five cases diagnosed by BALF analysis only, and identified co-pathogens.…”
Section: Discussionsupporting
confidence: 85%
“…However, the GM result in BAL fluid for A. flavus in our study (28/116, 24.1 %) is not comparable to the results from The Netherlands (3.44 %) [47], Italy (4.5 %) [48], USA (0.8 and 1.2 %) [36,39], Belgium (2.3 %) [7], France (2 %) [49], UK (0.6 %) [50], China (4 %) [33], Japan (0.6 %) [22], Czech and Slovak Republics (4.2 %) [51], Turkey (3.3 %) [52] and India (11.6 %) [46]. To the best of our knowledge, none of the previous studies reported a twofold mean of the GM index in IA patients with A. fumigatus in comparison to IA patients with A. flavus.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast Wingard's study evaluating prophylaxis with fluconazole and voriconazole in stem cell transplant patients and also another recently published study did not show any influence of mould‐active prophylaxis on GM positivity rate . Study design in the latter studies, however, differed markedly from Marr′s study as they both were primarily focussing on other objectives.…”
Section: Discussionmentioning
confidence: 82%